Evaluating Aid for Trade: A Survey of Recent Studies - Olivier Cadot; Ana Fernandes; Julien Gourdon; Aaditya Mattoo; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
The demand for accountability in "Aid-for-Trade" (AFT) is increasing but monitoring has focused on case-studies and impressionistic narratives. The paper reviews recent evidence from a wide range of studies, recognizing that a multiplicity of approaches is needed to learn what works and what does not.
Keywords: P45; O24; 330; "Aid for trade"; commerce